ANALYSIS OF COMMUNITY COMPLAINT HANDLING RESPONSIVENESS AS A STRATEGY FOR IMPROVING PUBLIC SERVICE QUALITY AT THE CIVIL SERVICE POLICE UNIT OF SUKOLILO DISTRICT, SURABAYA CITY - Zulianingsih, Nur; Devy Pramudiana, Ika; Roekminiati, Sri; Pramono, Sapto (International Journal of Multidisciplinary Reseach, 2025)
Modern public services increasingly emphasize high responsiveness. However, the Civil Service Police Unit (Satpol PP) of Sukolilo District faces significant challenges in managing public complaints due to the high dynamics of public order disturbances in an area with dense socio-economic activity. This study aims to analyze the responsiveness of complaint handling as a fundamental strategy for improving the quality of public services, and to identify determinant factors that hinder the effectiveness of service recovery mechanisms at the district level. Employing a qualitative approach with a case study design, the research explores the dynamics of street-level bureaucracy. Data were collected through in-depth interviews with structural officials, field officers, and reporting citizens, complemented by participatory observation of service processes and a review of Standard Operating Procedure (SOP) documents. The analysis integrates service quality and complaint management theories to examine the dimensions of responsiveness and procedural reliability within the law enforcement ecosystem. The findings indicate that officers’ responsiveness remains suboptimal, as the actual average response time frequently exceeds the 1×24-hour standard due to resource constraints and the exercise of discretion that tends to be reactive to social media pressure (viral-based response). The service recovery mechanism is still partial and does not consistently address root causes, directly contributing to stagnant levels of public satisfaction. The study concludes that systemic transformation is essential, recommending real-time integration of digital complaint channels with patrol units and the adoption of a collaborative approach based on community participation to achieve adaptive and accountable services.